Chirp-Fourier transform for quadratic phase interference fringe analysis: Principles, method and application. (October 2020) - Guo, Yong; Yang, Li-Dong
Highlights: Discrete time CFT is applied to quadratic phase interference fringe analysis for breaking the restriction on resolution of DCFT. Only certain rows of Newton's rings instead of whole Newton's rings are required in the phase derivative estimation owing to the application of outlier detection algorithm. An optimization model is established to estimate the phase derivative of Newton's rings, and a simple and practicable technology is proposed to reduce the impact of mean intensity. The proposed parameter estimation method is successfully applied to measure the curvature radius of spherical surface. Abstract: Quadratic phase interference fringes are often encountered in optical measurement, its parameters estimation plays an important role in the interferometry field. This paper takes Newton's rings as a classical example of quadratic phase interference fringe, proposes a CFT-based method to estimate the parameters of Newton's rings. The phase derivative can be estimated directly and accurately without unwrapping, which are verified by the simulated and actual Newton's rings. Furthermore, the proposed CFT-based method is applied to measure the curvature radius of spherical surface, which makes the measurement method has the advantages of low computational complexity, high accuracy and fast speed. The experiments results confirm that the CFT-based method not only has better noise and obstacle robustness over traditional Newton's rings measurement, but also has higher efficiency over FRFT-based method.